Triangel Concept Learning Design Using Palembang Cultural for Class VII Students - Ica Ramadona; Riza Agustiani; Atika Zahra; Agustiani Dumeva Putri (Jurnal Gantang, 2023)
The triangle is still a topic worth discussing because many pupils still want assistance in comprehending the notion of triangles as a whole. The research aims to produce a triangular concept learning design using the Palembang cultural context for VII grade students with augmented reality technology. The research subjects comprised 19 students from Class VII of Al-Azhar 33 Islamic Middle School in Palembang. The method used is design research, divided into preparing for the experiment, and design experiment, divided into two cycles, namely pilot experiments and teaching experiments, and finally, retrospective analysis. The data in this research was collected by observation, interview, documentation, and test. The instruments used in this research are video and field notes for observation and interview, LAS for documentation, and post-test for test. The data analysis technique is descriptive qualitative. The final result of this study is Local Instruction Theory (LIT) which contains the learning process in 4 activities, namely describing the triangles of the Musi 6 Bridge, identifying the properties of triangles based on side lengths, identifying the properties of triangles based on the size of the angles and solving problems related to the properties of triangles based on the length of the sides and the size of the angles. The results show that the cultural defined context can be used as a reference point in triangle material in class VII SMP.